2012
DOI: 10.1186/1477-7827-10-14
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol promotes expression of SIRT1 and StAR in rat ovarian granulosa cells: an implicative role of SIRT1 in the ovary

Abstract: BackgroundResveratrol is a natural polyphenolic compound known for its beneficial effects on energy homeostasis, and it also has multiple properties, including anti-oxidant, anti-inflammatory, and anti-tumor activities. Recently, silent information regulator genes (Sirtuins) have been identified as targets of resveratrol. Sirtuin 1 (SIRT1), originally found as an NAD+-dependent histone deacetylase, is a principal modulator of pathways downstream of calorie restriction, and the activation of SIRT1 ameliorates g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
116
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(133 citation statements)
references
References 36 publications
6
116
2
3
Order By: Relevance
“…However, it has been reported that resveratrol inhibits aromatase production in cultures of rat granulosa cells in vitro (53) and thus reduces the estrogen synthesis that leads to impaired folliculogenesis. In this context, it has been suggested that SIRT1 activation by resveratrol results in a significant increase of LH receptors in granulosa cells (62), and this polyphenol shows higher affinity for estrogen receptor (ER)-b (63) than for ER-a. Because LH is the main hormone responsible for ovulation, and actions mediated via interaction with ER-b may enhance ovulatory response (64), an alternative hypothesis for our results is that resveratrol could improve the ovulation rate through these receptors.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that resveratrol inhibits aromatase production in cultures of rat granulosa cells in vitro (53) and thus reduces the estrogen synthesis that leads to impaired folliculogenesis. In this context, it has been suggested that SIRT1 activation by resveratrol results in a significant increase of LH receptors in granulosa cells (62), and this polyphenol shows higher affinity for estrogen receptor (ER)-b (63) than for ER-a. Because LH is the main hormone responsible for ovulation, and actions mediated via interaction with ER-b may enhance ovulatory response (64), an alternative hypothesis for our results is that resveratrol could improve the ovulation rate through these receptors.…”
Section: Discussionmentioning
confidence: 99%
“…NAMPT is the rate-limiting enzyme in NAD biosynthesis, and it plays a critical role in several mammalian physiological processes (Revollo et al 2004, Imai 2009). In mammals, NAMPT regulates the activity of the sirtuin 1 (SIRT1) histone deacetylase (Revollo et al 2004), and it has been shown to be involved in the regulation of steroidogenesis (Morita et al 2012, Wu et al 2012. Sirtuins have not yet been identified in hen ovaries, but they may play a role in the effects of NAMPT on hen granulosa cell steroidogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that SIRT1 protein was expressed in mouse ovarian tissues (Morita et al, 2012), human luteinized granulosa cells (Benayoun et al, 2011) and bovine oocytes (Ghinis-Hozumi et al, 2011). The present study showed that SIRT1 protein was widely expressed in porcine ovary.…”
Section: Discussionmentioning
confidence: 97%
“…SIRT1 can reduce ovarian cell viability, promote ovarian progesterone (P 4 ) release and expression of luteinization-related genes in the ovary of rodents (Morita et al, 2012). Meanwhile, transfection of cells with SIRT1 gene increased the accumulation of proliferation markers (Cdc2/p34, cyclin B1), decreased accumulation of p50 and p65, and stimulated release of IGF-I in porcine ovary (PavlovĂĄ et al, 2013).…”
Section: Discussionmentioning
confidence: 98%